IMPLEMENTASI PROGRAM SEMBAKO PADA MASA PANDEMI COVID-19 DI NAGARI BATIPUAH ATEH KECAMATAN BATIPUH - Rifani, Robbi; Magriasti, Lince (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The purpose of this study was to determine the implementation of the Program Sembako in Nagari Batipuah Ateh and to find out the obstacles in its implementation. Determination of informants using purposive sampling technique and the form of checking the validity of the data with triangulation techniques. Techniques and data collection through interviews and documentation. This research is a quasi-qualitative. This research uses Richard E. Matland's implementation model. The results of this study indicate that the implementation of the Program Sembako is quite optimal. However, there are still some obstacles that occur in the process of implementing the basic food program in Nagari Batipuah Ateh.